Pengaruh Kualitas Layanan Inti dan Tambahan terhadap Positive Word of Mouth di SMU Semarang - Nuryatno, Yulius Jatmiko (Jurnal Ilmiah Aset, 2011)
Every company will face tight competition with other companies. One of the best efforts to keep and get customers is by managing core service quality, peripheral service quality and word of mouth. This research was done to examine the influence of the core service quality and peripheral service quality to the positive word of mouth. The object of the research was students of SMA Sint Louis Semarang. The sampling technique used was proportional sampling. The samples were 81 samples. The data collection was obtained by distributing questionnaire to the students. The data survey was organized by using regression analysis assisted by SPSS program. The result showed that independentvariable of the core service quality positively and significantly influence the positive word of mouth, while independent variable of peripheral service quality positively influence but not significantly to the positive word of mouth. It means the first hypothesis (H1) proposed was accepted. The limitation of the research was because some respondents did not answer the open questions, so the researcher hardly finds out the respondents wants to the service quality expected in SMA Sint Louis.